Changes in volumes and severity of surgical urgencies during the first two COVID-19 pandemic waves in a regional hospital network. - Carrara, Alessandro; Amabile, Dalia; Pertile, Riccardo; Reich, Federico; Nava, Francesca Laura; Moscatelli, Paolo; Pellecchia, Luigi; Motter, Michele; Zappalà, Orazio; Ghezzi, Gianmarco; Benetollo, Pierpaolo; Tirone, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Background and aim This study analyses the impact of the first two pandemic waves on surgical urgencies/emergencies and their consequences on an entire provincial hospital network's surgical activities.Methods  Clinical and epidemiological data of urgent/emergent surgical admissions and interventions in the Autonomous Province of Trento's hospital network were collected from the internal common electronic database. The investigation periods were March-May 2019 (reference period), March-May 2020 (phase-I), June - August 2020 (phase-II), and October - December 2020 (phase-III). The same data were divided and grouped for the six most represented diagnoses.Results: The number of admissions for surgical emergencies in the studied periods showed a sinusoidal trend. In the reference period of 2019, 957 patients were admitted in urgency, while in the three pandemic phases, urgent admissions were 511, 888 and 633 respectively (-47% in phase I, - 8% in phase II, -34% in phase III). This trend was also observed by stratifying admissions for single disease, except for gastrointestinal perforations and pancreatitis, which showed a slight increasing trend in phase-I. Among the studied population, the surgical rate was 35.2% in phase-I and 34.3% in phase-III; these data were significantly higher than in 2019 (25.6%). Conclusions The effect of the COVID pandemic on surgical emergencies and urgencies (SUEs) was mainly indirect, manifesting itself with a significant reduction in the number of surgical admissions, particularly in phases-I and-III. Conversely, in the same phases, the surgical rate showed a significant increase compared to 2019.